2010
DOI: 10.1002/acp.1677
|View full text |Cite
|
Sign up to set email alerts
|

Counting during recall: Taxing of working memory and reduced vividness and emotionality of negative memories

Abstract: While initially subject to debate, meta-analyses have shown that eye movement desensitization and reprocessing (EMDR) is effective in the treatment of posttraumatic stress disorder (PTSD). Earlier studies showed that eye movements during retrieval of emotional memories reduce their vividness and emotionality, which may be due to both tasks competing for limited working memory (WM) resources. This study examined whether another secondary task that taxes WM has beneficial effects, and whether the stronger the ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
76
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 16 publications
11
76
1
5
Order By: Relevance
“…An alternative to the orienting response is that to store trauma memories in an episodic form taxes working memory and that eye movements competes with such memories for the limited storage capacity which then results in reductions in vividness and subsequently emotional ratings (I. M. van den Hout et al, 2011;van den Hout et al, 2010) EMDR is efficacious for PTSD and trauma patients with or without co-morbid depression and requires little -to-no between session tasks to ensure positive outcomes. This evidence can be added to the growing list of differences between EMDR and CBT that others have also noted including the way exposure is employed in each of the 2 treatment modalities, EMDR's non-directive approach, and the encouragement of free association during trauma recall and distancing.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative to the orienting response is that to store trauma memories in an episodic form taxes working memory and that eye movements competes with such memories for the limited storage capacity which then results in reductions in vividness and subsequently emotional ratings (I. M. van den Hout et al, 2011;van den Hout et al, 2010) EMDR is efficacious for PTSD and trauma patients with or without co-morbid depression and requires little -to-no between session tasks to ensure positive outcomes. This evidence can be added to the growing list of differences between EMDR and CBT that others have also noted including the way exposure is employed in each of the 2 treatment modalities, EMDR's non-directive approach, and the encouragement of free association during trauma recall and distancing.…”
Section: Discussionmentioning
confidence: 99%
“…Horizontal eye movements indeed tax working memory (Engelhard et al, 2010b;Van den Hout et al, 2011). In line with the working memory account, analogue studies have found that other taxing tasks during recall also reduce vividness and/or emotionality of negative memories, like vertical eye movements, drawing a complex figure (Gunter & Bodner, 2008), verbal arithmetic (Kemps & Tiggemann, 2007), mental arithmetic (Engelhard, van den Hout, & Smeets, 2011;Van den Hout et al, 2010; but see a clinical study by Lilley, Andrade, Turpin, Sabin-Farrell, & Holmes, 2009), and playing the computer game Tetris (Engelhard et al, 2010b). Interestingly, Holmes, James, Coode-Bate, & Deeprose (2009) found that playing Tetris shortly after viewing a film with traumatic content reduces flashbacks in the next week, which suggests that a taxing visuospatial task during memory consolidation may be an effective preventative intervention.…”
mentioning
confidence: 92%
“…Interestingly, Holmes, James, Coode-Bate, & Deeprose (2009) found that playing Tetris shortly after viewing a film with traumatic content reduces flashbacks in the next week, which suggests that a taxing visuospatial task during memory consolidation may be an effective preventative intervention. Further support for the working memory theory comes from studies showing that people with less working memory capacity or more taxing of working memory show more benefits from dual-tasks during memory recall (Gunter & Bodner, 2008;Van den Hout et al, 2010).…”
mentioning
confidence: 97%
“…It has been consistently demonstrated that performance deteriorates when two tasks make demands on the same WM resources, indicating that WM has limited capacity. Focussing on a memory (van Veen et al, 2015) and engaging in EM, both tax WM resources (Engelhard, van Uijen, & van den Hout, 2010; van den Hout et al, 2011, 2010). Simultaneously performing these tasks therefore reduces the sensory quality of the memory, making it less vivid and less emotional.…”
mentioning
confidence: 99%
“…Using this laboratory design, different variables can be manipulated in order to examine the underlying working mechanisms of EMDR. Studies that have adopted the model have shown, for example, that memories are not only degraded by EM, but also by other WM taxing dual tasks, such as complex counting (van den Hout et al, 2010) and mindful breathing (van den Hout et al, 2011), and that not only negative memories can be altered by EM, but also positive memories (Engelhard et al, 2010; Hornsveld et al, 2011; Littel, van den Hout, & Engelhard, 2016), providing evidence for the abovementioned WM account.…”
mentioning
confidence: 99%